Peran Locus of Control Sebagai Variabel Intervening: Pengaruh Literasi Keuangan dan Persepsi Risiko Terhadap Keputusan Investasi - Khadijah, Sitti; Fajriah, Yana; Heslina, Heslina (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to explore the effect of financial literacy and risk perception on investment decisions with locus of control as a mediating variable in STIEM Bongaya Makassar Student Investment Gallery Investors. Data collection using primary data obtained from questionnaires using total sampling technique so that 58 units of analysis (respondents) were obtained. The results of data processing using SmartPLS 3.0. Provides evidence that financial literacy and locus of control have a positive and meaningful effect in improving student investment decisions, on the other hand risk perception has a negative and real effect on investment decisions, financial literacy has a positive effect but can not increase locus of control, different conditions are shown with risk perception, that risk perception is proven to have a positive and meaningful effect on locus of control. The results of indirect effect testing show that locus of control cannot mediate the effect of financial literacy and risk perception on investment decisions.